A study on the attitudes and preferences on PPSMI abolishment among teachers in SK. Tumunda Salimandut / Mohd Ikhwan Mohd Asdi - Mohd Asdi, Mohd Ikhwan (2010)
English Language in Mathematics and Science (ELIMS), or in Malay language, Pengajaran dan Pembelajaran Sains dan Matematik dalam Bahasa Inggeris (PPSMI), is an official name for one of the educational policy in Malaysia. This policy had announced and enact that English language will replace Malay language/ mother tongue as a medium of instruction for the subject of Mathematics and Science in all level of educational system. Since the introduction and implementation of this policy by the administration of former Malaysian prime minister Tun Dr. Mahathir Mohamad in year 2003, it had always become the heat debated issue. Finally on 8 of July 2009, it was decided that this policy will be abolished in year 2012, as announced by the Minister of Education Tan Sri Muhyidin Yassin after depth study and researches had been done to measure the relevance of the policy. According to the description of the policy PPSMI on the website of the Ministry of Education Malaysia: Rational transition to language teaching and learning in Science and Mathematics from Malay to English language are government concerns towards the development of human resources to achieve developed nation status and preparation from the early stage of school to compete in the era of globalization.